THE WELFARE OF MASJID’S MARBOT IN SURABAYA BASED ON THE MAQASHID SYARIAH PERSPECTIVE - Gilang Abdu Baasithurahim; Irham Zaki (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The purpose of this study was to find out how the welfare of mosques’ marbot in Surabaya from the perspective of maqashid syariah. Research on welfare is based on the phenomenon that occurs in research subjects. The subject of this research is the mosques’ marbot located in Surabaya by taking 4 mosques as the  samples with the most number based on typology. This research uses a qualitative method with a descriptive approach. After the interview, the results of the study were analyzed using descriptive data analysis techniques by narrating the results of the interview and direct narration. The findings of this study are the welfare of the mosques’ marbot can not be said to be fully prosperous because many aspects have not been fulfilled, but for the mosques’ marbot not only measures sustenance based on material ownership alone but also peace of mind that is obtained because they are always close to the mosque. On the other hand, the mosques have also provided rewards and facilities that are considered appropriate to support the life and performance of the mosques’ marbot.Keywords: welfare, mosque marbot, sharia maqashidREFFERENCEAl-Faruq, Asadullah. (2010). Panduan lengkap mengelola dan memakmurkan masjid. Solo: Pustaka Arafah.Al-Fauzan, A. b. (2008). Fiqih seputar masjid, penerjemah Ahmad Yunus. Jakarta: Pustaka imam syafi’i.Athiyyah, Muhyi al Din. (1992). Al kasysyaf al iqtishadi li ayat al qur’an al karim. Riyadh: Al Dar al Ilmiyah Lil Kitab al Islami.Bakri, Asyafrijaya. (1996). Konsep maqashid syariah menurut Assyatibi. Jakarta: Lentera Abadi. Chapra, M. Umer. (2000). Islam dan pembangunan ekonomi, edisi terjemahan. Jakarta: Gema Insani Press.Chapra, Umer. (2001). Masa depan ilmu ekonomi (Sebuah tinjauan Islam). Jakarta: Gema Insani Press.Dewan masjid Indonesia. (2003). Buku panduan praktis manajemen pengelolaan masjid, edisi pertama. Surabaya: PW DMI Jawa Timur.